MAKNA GAYA HIDUP HEDONISME DI KALANGAN SISWA SMA NEGERI 9 PEKANBARU - Tarigan, Efraim Arapenta; Yozani, Ringgo Eldapi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study discusses the hedonistic lifestyle among students of SMAN 9 Pekanbaru, characterized by a tendency to prioritize pleasure in daily life. The purpose of this study is to reveal the meaning of a hedonistic lifestyle from the perspective of past motives (because motive) and future motives (in order to motive). The research uses a qualitative method with a phenomenological approach. Informants were selected purposively, and data were collected through interviews, observations, and documentation. Data analysis involved data collection, reduction, presentation, and drawing conclusions. Data validity was tested through prolonged engagement and triangulation. The findings show that the hedonistic lifestyle arises from past experiences, such as a lack of recognition in social environments. This motivates students to seek acknowledgment and popularity through a consumptive lifestyle. Additionally, hedonism is seen as a way to achieve higher social status and an ideal standard of living as portrayed by influencers, and as preparation for attaining their dream careers. Keywords: Hedonism, Lifestyle, Students, Social Motives, Phenomenology, SMAN 9 Pekanbaru.